Cutoff value for predicting success in triathlon mixed team relay - Ledanois, T.; Hamri, I.; De Larochelambert, Q.; Libicz, S.; Toussaint, J. F.; Sedeaud, A. (Frontiers in Sports and Active Living, 2023)
Introduction: The Mixed-Team-Relay (MTR) triathlon is an original race format present on the international scene since 2009, which became an Olympic event at the Tokyo 2020 Games. The aim of this study was to define the probabilities of reaching a victory, a podium, or a finalist rank in a relay triathlon, according to the position of any of the four relayers (Women/Men/Women/Men) during each of the four segments (leg) of the race.